2017
DOI: 10.1016/j.ymgmr.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cognitive functioning in individuals with tyrosinemia type 1 treated with nitisinone and protein-restricted diet

Abstract: IntroductionTyrosinemia Type 1 (HT1) is an autosomal recessive disorder caused by a defect in the enzyme fumarylacetoacetate hydroxylase in the tyrosine pathway. Implementation of nitisinone (NTBC) treatment has dramatically improved survival rate of individuals with HT1, yet recent reports on cognitive impairment in treated patients exist.AimsDescribe long-term neurocognitive outcome individuals with HT1 treated with nitisinone and protein restricted diet.MethodologyTwelve individuals with HT1 were analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 16 publications
(24 reference statements)
4
36
0
Order By: Relevance
“…The strong correlation between recent tyrosine concentrations and levels of inattention, and the even more robust correlation when correcting for age at diagnosis, support the notion that transient concentration of tyrosine could be more relevant for levels of inattention than long‐term concentrations, and that these effects are not directly attributed to nitisinone itself. Garcia, de la Parra, Arias, Arredondo, and Cabello () reported a decline in IQ (mean of 16.8 IQ points) over minimum 2 years in patients receiving a diagnosis before 8 months of age (with first symptom appearing between the first and third months). Bendadi et al () also found a decline in IQ in a group with HT‐1 who were 8 months or younger when receiving the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The strong correlation between recent tyrosine concentrations and levels of inattention, and the even more robust correlation when correcting for age at diagnosis, support the notion that transient concentration of tyrosine could be more relevant for levels of inattention than long‐term concentrations, and that these effects are not directly attributed to nitisinone itself. Garcia, de la Parra, Arias, Arredondo, and Cabello () reported a decline in IQ (mean of 16.8 IQ points) over minimum 2 years in patients receiving a diagnosis before 8 months of age (with first symptom appearing between the first and third months). Bendadi et al () also found a decline in IQ in a group with HT‐1 who were 8 months or younger when receiving the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we thank the physicians, nursing staff, and metabolic departments of all collaborating Academic Medical Center, Amsterdam, Netherlands. 9 The NIHR Great Ormond Street Hospital Biomedical Research Centre (BRC ), London, UK.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…However, recent studies suggest that the neurocognitive outcome of NTBC-dietary-treated TT1 patients is suboptimal [5][6][7][8][9][10][11]. Lower IQ values have been observed along with impairment in various cognitive domains, including executive functioning and social cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The management of hereditary tyrosinemia type 1 (HT1) has been revolutionized by the introduction of 2‐(2‐nitro‐4‐trifluoromethylbenzoyl)‐1‐3‐cyclohexanedione (NTBC) . Continued NTBC treatment after liver transplantation (LT) has been suggested as a means of controlling renal succinylacetone (SA) production and hence improving long‐term renal function .…”
mentioning
confidence: 99%
“…A factor to consider is that even low‐dose NTBC causes significantly raised tyrosine, raising the issue of whether reintroduction of dietary restriction would be necessary. Furthermore, some patients with HT1 treated with NTBC and protein‐restricted diet are at risk of developmental delay and impaired cognitive functioning . We describe here the case of a HT1 patient who was allowed an unrestricted diet without NTBC after living‐related donor LT.…”
mentioning
confidence: 99%